VD_FINDINFO Arrêt / 2016 / 805 vom 30. August 2016 - VD Tribunal cantonal (2016)
AUTORITÉ PARENTALE CONJOINTE, ADMISSION DE LA DEMANDE, DROIT D'ÊTRE ENTENDU | 298b al. 1 CC, 298b al. 2 CC, 450 CC, 29 al. 2 Cst.